EFEKTIVITAS PENGGUNAAN APLIKASI GOOGLE CLASSROOM DALAM PEMBELAJARAN FISIKA DI MASA PANDEMI COVID-19 DI SMA SANTA MARIA DELLA STRADA JAKARTA - Septina Severina Lumbantobing; Manogari Sianturi; Sartika Ari Veronica Simbolon; Isvan Ruan Saputra Samaloisa; Etiwa Safitri Saleleubaja (Jurnal Manajemen Pendidikan, 2022)
The Google Classroom application is one form of the learning management system that is most widely used by students. This is because this application is easy to use and does not require large application storage space on both smartphones and laptops. The purpose of this study was to determine the effectiveness of using the Google Classroom application in learning physics during the COVID-19 pandemic. This research method uses descriptive quantitative research methods. The research instrument used was a questionnaire given to 60 students consisting of class X and class XI. Indicators of effectiveness in this study are 1) understanding of the material in learning by using google classroom, 2) ease of accessing the google classroom application, 3) communication while using the google classroom application while online, 4) the use of google classroom in physics practicum. The results showed that as many as 61.85% of students agreed that it was easy to understand the material/learning theory by using google classroom, 72.5% of students agreed to the ease of accessing the google classroom application, 64.9% of students agreed that communication was smooth with the use of google classroom. and 40.67% of students agree that it is difficult to carry out practicum with the google classroom application alone without the help of other applications. Overall the effectiveness of using the Google Classroom application in learning physics is in the high category with a percentage of 70% which means it is effectively used by teachers and students